Braille display systems for blind people with haptic belt - Kamarudin, Muhammad Nizam; Hairi, Mohd Hendra; Aboali, Maged Yahya Ali Hussein; Mohd Shah, Hairol Nizam; Mohd Aras, Mohd Shahrieel; Md. Rozali, Sahazati (Penerbit Universiti Teknikal Malaysia Melaka, 2021)
This manuscript addresses the development of a microcontroller-based braille display system. Recently, tactile display devices use technologies such as electric motors, piezoelectric, and solenoids as actuators. Nevertheless, the device is seeming to be bulky, inflexible, and far from soft actuation. Thus, the project in this manuscript portrays the development of a new design by using Micro servomotors and embedded soft-computing algorithms. The system consists of a haptic belt and a sensing unit. The sensing part of a Braille cell is designed to be wearable on arm. The methodology to reach the outcomes involving the ATmega328P microcontroller in the Arduino board, Tower Pro SG51R micro servo, and the LV-MaxSonar-EZ1 ultrasonic sensor. These apparatuses are lumped in a Braille Display System with a Haptic Belt. The performance and functionality of the system are evaluated based on its ability to detect obstacles from four different locations by means of ultra-sonic sensors. The sensors actuate the servomotors to notice the blind. The system works well around 0.5 meters radius. The boundedness of the system radius is acceptable to secure ample time for the scanning process. The responses of the sensors upon various obstacles are presented in this manuscript with a thorough analysis.